The magnetic field dependency of hydrogenic impurity binding energy under inverse lateral parabolic potential - YAHŞİ, UĞUR (ELSEVIER, 2008)
We calculated the magnetic field dependency of hydrogenic donor binding energy in cylindrical quantum wires under inverse lateral parabolic potential. We have worked in the effective mass approximation and variational calculation scheme. We have found there is an abrupt change in binding energy with the magnetic field strength, and the results are compared with square quantum wire binding energies. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Quantum well wire; Inverse parabolic potential; Impurity binding energy; Magnetic field; QUANTUM-WELL WIRES; EPITAXIAL GAAS FILMS; TRANSITION ENERGIES; STATES; PARALLEL; GROWTH